EVALUASI STRATEGI PROGRAM PENANAMAN KEMBALI PERKEBUNAN KELAPA SAWIT PADA PERKEBUNAN GOLDEN AGRI RESOURCES (SINARMAS GRUP) - , Nurjanah Sekar Wijayanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sinarmas Plantation Management has set a relatively new strategy, which is the replanting strategy of palm oil plantations, in order to manage the sustainability of CPO production growth in the future. This study evaluated the feasibility strategy on the production aspect of the company. Research methodology is using analysis of the company's internal and external of the palm oil industry using the Herfindahl Hirschman Index analysis tools, Porter's Five Forces Analysis, PEST, Driving Forces, Key Success Factor. The results of the internal analysis shows that if Sinarmas Plantation-which is an integrated palm oil company, implementing replanting strategy starting in 2013, the total projected CPO production began to increase in 2019 and even exceeding, comparing to the option not to do replanting strategy. The projected number of average land productivity will be 5.8 ton of CPO per hectare, in line with the company's mission and operational targets set out in â2020 Master Plan Productionâ. From the external aspect of the analysis showed that palm oil plantations market is controlled by a few major players, Indonesia and Malaysia. The CPO industry still projected to be prospective in the near future. Thus, based both on the analysis, the replanting strategy is a feasible option to be taken by Sinarmas Plantation.